A study of some factors affecting surface culture production of citric acid from cane sugar by a Philippine strain of Aspergillus niger B-65 - Diokno-Palo, Natividad; Cunanan, Lourdes F.; Danguilan, Maria L. (1984)
A black mold identified as apergillus niger and designated as A. niger B-65 was single out from 300 mold isolates, obtained from rotting fruits and vegetables, for its citric acid-producing capacity superior to those of foreign molds: A. niger NRRL 3,A. niger 599 and Rhizopus stolonifer NRRL-1477. Highest yield of citric acid was produced after 12 days when A. niger B-65 was cultivated by surface method in modified Shu and Johnson medium, containing 12& sucrose, 0.4125% (NH4)2S04 and 2.5 mL of 2x10 5 spores/mL inoculum mL of medium adjusted to pH 2.0.